Seasonal Dynamics of Organic Carbon and Nitrogen in Biomasses of Microorganisms in Arable Mollisols Affected by Different Tillage Systems - Yuriy S. Kravchenko; Xingyi Zhang; Chunyu Song; Wei Hu; Anna V. Yarosh; Olena V. Voitsekhivska (Land, 2022)
Tillage has been reported to induce seasonal changes of organic carbon (Cmicro) and nitrogen (Nmicro) in the biomass of microorganisms. Soil microorganisms execute such ecosystem functions as it is an immediate sink of labile biophil elements; it is an agent of a conversion, catalysis and synthesis of humus substances; it transforms soil contaminants into nonhazardous wastes and it participates in soil aggregation and pedogenesis as a whole. However, the seasonal turnover of microorganisms on arable lands in temperate ecosystems has not been studied at a relevant level. Hence, we are aimed at studying the dynamics of such soil microbial biomass patterns as Cmicro, Nmicro, microbial index (MI = (Cmicro/CTOC)·100%) and CO2-C emissions against the background of 9 years of tillage and 22 years of abandoned (Ab) and fallow (F) usage. Our study was conducted on a long-term experimental site on a Mollisol in Northeast China. The maximum Cmicro and Nmicro contents were recorded at the beginning of the growing season at the 0–10-cm layer and mid-July at the 20–40-cm layer, while the minimum content was during August–October. The Cmicro content ranged from 577.79 to 381.79 mg−1 kg−1 using Ab in the spring to 229.53 to 272.86 mg−1 kg−1 in the autumn using CT (conventional tillage) and F in the 0–10- and 10–20-cm layers, respectively. The amplitude of Nmicro content changes were several times lower as compared with the Cmicro. The smallest quartile range (IQR0.25–0.75) of such changes was shown when using the following treatments: no till (NT) and Ab in the 0–10-, NT and F in the 10–20- and CT in the 20–40-cm layer. The widest Cmicro:Nmicro ratio was recorded at F and CT in the 0–20- and CT and rotational tillage (Rot) in the 20–40-cm layer. The MI dynamics were similar to the trends of Cmicro and Nmicro and changed from 0.72 ± 0.168 to 2.00 ± 0.030%. The highest share of Cmicro in CTOC was at Ab (1.82 ± 1.85%) and NT (1.66 ± 1.52 %) in the 0–10-, Ab (1.23 ± 1.27%) and NT (1.29 ± 1.32%) in the 10–20- and Ab (1.19 ± 1.09%) and F (1.11 ± 1.077%) in the 20–40-cm layer, correspondingly. The Pearson’s correlation coefficient between Cmicro and CTOC increased from the upper 0–10- to the lower 20–40-cm layer; it was “strong” and “high” between Cmicro and CTOC. Different uses of Mollisol affected the amplitude of the Cmicro and Nmicro seasonal changes, but it did not change their trend. Our results suggest the key role of Ab and NT technologies in Cmicro accumulation in the total organic carbon (TOC).